Design and development of anonymous location based routing for mobile ad-hoc network - Swetha Mahendrakar Shaymrao; Pushpa Sothenahalli Krishnaraju; Thungamani Mahalingappa; Manjunath Thimmasandra Narayanappa (Institute of Advanced Engineering and Science, 2022)
Mobile ad-hoc network (MANET) consists of wireless nodes interacting with each other impulsively over the air. MANET network is dynamic in nature because of which there is high risk in security. In MANET keeping node and routing secure is main task. Many proposed methods have tried to clear this issue but unable to fully resolve. The proposed method has strong secure anonymous location based routing (S2ALBR) method for MANET using optimal partitioning and trust inference model. Here initially partitions of network is done into sectors by using optimal tug of war (OTW) algorithm and compute the trustiness of every node by parameters received signal strength, mobility, path loss and co-operation rate. The process of trust computation is optimized by the optimal decided trust inference (ODTI) model, which provides the trustiness of each node, highest trust owned node is done in each sector and intermediate nodes used for transmission. The proposed method is focusing towards optimization with respect to parameter such as energy, delay, network lifetime, and throughput also above parameter is compared with the existing methods like anonymous location-based efficient routing protocol (ALERT), anonymous location-aided routing in suspicious MANET (ALARM) and authenticated anonymous secure routing (AASR).